Existing psychological supportive care interventions for cervical cancer patients: a systematic review and meta-analysis - Kamala Dhakal; Changying Chen; Panpan Wang; Joanes Faustine Mboineki; Bibhav Adhikari (BMC, 2024)
Abstract Cervical cancer patients commonly experience psychological supportive care needs, necessitating diverse interventions to enhance psychological well-being and alleviate physical symptoms. This systematic review, covering English-published articles from January 1999 to April 2023, assessed the impact of psychological supportive care interventions on anxiety and depression. Twenty-Six studies, including 11,638 patients, were analyzed, comprising randomized controlled trials; quasi-experimental, and pre-post-test designs from PubMed; Science Direct; Wiley online library; Google Scholar; Cochrane Library; and JSTOR. The extraction of data was done by two independent authors and a third independent author checked the data extraction. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), 2020 statement was adopted. The population, intervention, comparator, and outcomes (PICO) search strategy was applied. Effective Public Health Practice Project (EPHPP) tool was used to assess the quality of selected articles. Various interventions, such as psychological nursing, exercise, counselling, psycho-curative approaches, peer and family education, psychotherapy, and medication, were identified. Two studies incorporated homework sessions, predominantly administered by nursing staff. Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) were commonly used instruments. Statistical analysis revealed a significant difference in anxiety and depression scores between treatment and control groups (p < 0.005) post-intervention across all studies. A subsequent meta-analysis of eight homogeneous studies, utilizing a random-effects model, showed a moderate-to-high overall effect size (1.35, 95% CI: 0.75 to 1.94), indicating a statistically significant positive impact. Various studies exhibited variability in effect sizes ranging from low to high. While the meta-analysis included 936 participants, the forest plot visually represents individual study effect sizes and the combined effect size. Preliminary evidence supports the positive impact of psychological supportive care interventions on cervical cancer outcomes, urging further research, especially exploring long-term effects and employing rigorous study designs.